Respuesta :

Answer=0

Step-by-step explanation:

Greetings !

Firstly, plug in give values of the variables to the expression

[tex]( \frac{8}{4} ) {}^{2} - \frac{16}{8 - 4} [/tex]

apply exponent rule

[tex]( \frac{a}{b} ) {}^{c} = \frac{a {}^{c} }{b {}^{c} } [/tex]

[tex] \frac{8 {}^{2} }{4 {}^{2} } = \frac{64}{16} = 4[/tex]

Whereas for the second expression

[tex] \frac{16}{8 - 4} = \frac{16}{4} = 4 [/tex]

Thus, subtract the numbers

[tex]4 - 4 = 0[/tex]

Hope it helps!

Answer: 0

Step-by-step explanation:

To solve this problem, plug in. In other words, replace all of the letters with the given numbers. (this is also called substitution, I just described it this way to simplify it).

"a" becomes 8

"b" becomes 4

"c" becomes 16

PEMDAS= Parenthesis, Exponents,Division, Addition, Subtraction

(8/4)² - 16/8-4

2² - 16/8-4

4 - 16/8-4

4 - 16/4

4 - 4 = 0

Hope this helps!! :D

attachment, for reference:

Ver imagen zionknyc